Dampak Penggunaan Media Sosial terhadap Kesehatan Mental Remaja: Analisis Faktor Risiko dan Protektif dalam Konteks Psikologi Klinis Sosial - Zulfa, Intan Nala (Maliki Interdisciplinary Journal, 2025)
This study explores the complex relationship between social media use and adolescent mental health through a social clinical psychology approach. With the increasing prevalence of anxiety and depression disorders among adolescents alongside the massive adoption of digital platforms, this study aims to identify the factors that mediate the negative and positive impacts of social media on psychological well-being. Through a comprehensive literature review and a bio-psycho-social theoretical framework, the findings indicate that the quality of online interactions, duration of use, and individual personality characteristics play a significant role in determining mental health outcomes. Clinical implications include the development of more targeted interventions and community-based preventive approaches.